W.A.N.N Trading Corporation Sdn Bhd / Muhammad Fariz Muhammad Alias Teaw - Muhammad Alias Teaw, Muhammad Fariz (2020)
In the case study of Fundamental of Entrepreneurship (ENT300), I have decided to choose W.A.N.N TRADING CORPORATION SDN BHD as my study case. So, I go to the company to meet the manager and get the information about the business profile.to complete it. In addition, I do an interview session with the manager of the company. The manager’s name is Encik Muhammad Ali Bin Abbas.During the interview session, I have get all the information about the company to complete my case study. The manager answers all my questions when I ask her. This show the manager is a kind person. The information which she told me such as background of the business, organizational structure, type of business model, product or service marketing and operational strategy. Besides that, I also know the history of the company which how the company was began. From small to big company. Next, the product of company also a quite well-known among the youth and family. So, the product may become favourite food among them. Other than that, I also know the characteristic manager of company through the interview session. The characteristic should be example to the people. This is because it shows the good characteristic which can be possessed. Lastly, I also get the information about the company from social media. The social media such as Facebook really help me. From the page Facebook, many people give like and follow that pages. Number contact of company also display at that page. So, it will help people to call the company and ask any information about it.